β-catenin and IL-1β dependent CXCL10 production drives progression of disease in a mouse model of Congenital Hepatic Fibrosis - Kaffe, Eleanna (Hepatology, 2018)
Congenital Hepatic Fibrosis (CHF), a genetic disease caused by mutations in the PKHD1 gene, encoding for the protein fibrocystin (FPC), is characterized by biliary dysgenesis, progressive portal fibrosis, and by a PKA-mediated activating phosphorylation of β-Catenin at Ser675. Biliary structures of Pkhd1(del4/del4) mice, a mouse model of CHF, secrete CXCL10 a chemokine able to recruit macrophages. The aim of this study is to clarify whether CXCL10 plays a pathogenetic role in disease progression in CHF/CD and to understand the mechanisms leading to increased CXCL10 secretion. We demonstrate that treatment of Pkhd1(del4/del4) mice for three-month with AMG-487, an inhibitor of CXCR3 the cognate receptor of CXCL10, reduces the peribiliary recruitment of M2 macrophages (CD45(+)F4/80(+) cells), spleen size, liver fibrosis (Sirius red), and cyst growth (K19(+) area), consistent with a pathogenetic role of CXCL10. Furthermore, we show that in FPC-defective cholangiocytes, isolated from Pkhd1(del4/del4) mice, CXCL10 production is mediated by JAK/STAT3, in response to IL-1β and β-Catenin. Specifically, IL-1β promotes STAT3 phosphorylation whereas β-Catenin promotes its nuclear translocation. Increased pro-IL-1β was regulated by NF-kB and increased secretion of active IL-1β was mediated by the activation of NLRP3 inflammasome (increased expression of caspase 1 and NLRP33). CONCLUSIONS: In FPC-defective cholangiocytes, β-Catenin and IL-1β are responsible for STAT3-dependent secretion of CXCL10. In vivo experiments show CXCL10/CXCR3 axis prevents the recruitment of macrophages, reduces inflammation and halts the progression of the disease. The increased production of IL-1β highlights the autoinflammatory nature of CHF and may open novel therapeutic avenues.